La Casa de Bernarda Alba, Sistematización de la Experiencia Vivida del Montaje Conjunto 2019 – 2 Asumido Desde la Acomodación del Texto Dramático (2020)
The analysis of the “Montaje Conjunto 2019-2” experience about the adaptation of the dramatic text “La Casa de Bernarda Alba”, written by Federico García Lorca. Becomes the development of the systematization, in an study of the elements that influence the original work: (geography, time, historical events, context: social, political, cultural, and oral tradition); that create a set of analogies and divergences resulting in a new dramaturgy, approaching themes posed by the author in his work a "drama of Andalusian sexuality" Cervantes (sf) that led to an investigation of the role of women in the XX century and the revolutionary movements that took place in Spain - Region of Andalusia and Colombia - Andean region; the similarities against the context of the author as a social entity, the personal environment (his experiences) and the work; Finally the folklore of two divergent and analogous cultures is presented establishing a link in the way of preserving the tradition, transforming it and creating a staging of two unique cultural contexts.